SARS‐CoV‐2 Seroconversion in Humans: A Detailed Protocol for a Serological Assay, Antigen Production, and Test Setup. Issue 1 (17th April 2020) - Stadlbauer, Daniel; Amanat, Fatima; Chromikova, Veronika; Jiang, Kaijun; Strohmeier, Shirin; Arunkumar, Guha Asthagiri; Tan, Jessica; Bhavsar, Disha; Capuano, Christina; Kirkpatrick, Ericka; Meade, Philip; Brito, Ruhi Nichalle; et al.
Abstract: In late 2019, cases of atypical pneumonia were detected in China. The etiological agent was quickly identified as a betacoronavirus (named SARS‐CoV‐2), which has since caused a pandemic. Several methods allowing for the specific detection of viral nucleic acids have been established, but these only allow detection of the virus during a short period of time, generally during acute infection. Serological assays are urgently needed to conduct serosurveys, to understand the antibody responses mounted in response to the virus, and to identify individuals who are potentially immune to re‐infection. Here we describe a detailed protocol for expression of antigens derived from the spike protein of SARS‐CoV‐2 that can serve as a substrate for immunological assays, as well as a two‐stage serological enzyme‐linked immunosorbent assay (ELISA). These assays can be used for research studies and for testing in clinical laboratories. © 2020 The Authors. Current Protocols in Microbiology published by Wiley Periodicals LLC. Basic Protocol 1 : Mammalian cell transfection and protein purification Basic Protocol 2 : A two‐stage ELISA for high‐throughput screening of human serum samples for antibodies binding to the spike protein of SARS‐CoV‐2